Assessing Thomson's Model of Seasonal Change. (1st April 2014) - Allen, Harry; Rowe, Pam
Abstract: Donald Thomson's 1939 discussion of the effects of seasonality on Australian Aboriginal hunter gatherer subsistence has been acknowledged as a classic. Its title "The Seasonal Factor in Human Culture" reflects his argument that seasonality should be considered a part of human culture when archaeological interpretations are being made. Thomson wrote this critique of culture historical classification at the invitation of Grahame Clark, arguing that the seasonal cycle was a factor determining the location of Aboriginal camp sites and the activities performed at them. Placing the 1939 article alongside Thomson's long term interest in Aboriginal society, ecology, technology, and material culture allows us to see this as a pioneering work exploring human behavior and its archaeological signature.